Exact String Matching Algorithms: Survey, Issues, and Future Research Directions - Hakak, Saqib Iqbal; Kamsin, Amirrudin; Shivakumara, Palaiahnakote; Gilkar, Gulshan Amin; Khan, Wazir Zada; Imran, Muhammad (IEEE access, 2019)
String matching has been an extensively studied research domain in the past two decades due to its various applications in the fields of text, image, signal, and speech processing. As a result, choosing an appropriate string matching algorithm for current applications and addressing challenges is difficult. Understanding different string matching approaches (such as exact string matching and approximate string matching algorithms), integrating several algorithms, and modifying algorithms to address related issues are also difficult. This paper presents a survey on single-pattern exact string matching algorithms. The main purpose of this survey is to propose new classification, identify new directions and highlight the possible challenges, current trends, and future works in the area of string matching algorithms with a core focus on exact string matching algorithms.